A Localized Planarization Strategy in Hole Mobility Modulation of Disordered Triphenylamine‐Based Organic Semiconductors. Issue 12 (7th November 2021) - Zhang, Zewei; Zhu, Yanan; Wu, Yuting; Zhao, Chongguang; Meng, Hong
Abstract: Hole mobility plays a critical role in organic semiconductors, which is synergistically controlled by many factors closely interrelated to the molecular configuration, for example, the degree of molecular planarization. But at present, analysis from quantitative ab initio models to assess this correlation is lacking. Here, a series of triphenylamine‐based materials are designed and investigated to build a system with different levels of planarization. The key parameters in the Marcus equation are calculated with quantum and molecular mechanics methods and the hole mobilities are evaluated. Compared with non‐planar and fully planar molecules, localized planar molecules exhibit low reorganization energy, high transfer integral, and moderate energy disorder. Considering the conjugation and rigidity effects, a localized planarization strategy is demonstrated to design functional triphenylamine‐based materials by keeping a balance of the three factors above and enhanced hole mobilities are predicted. This strategy will shed light on mobility optimization and the applications of triphenylamine‐based materials. Abstract : This work reveals the correlation between molecular planarity to hole mobility in a specific triphenylamine‐based material system. After a standardized quantum and molecular mechanics method and kinetic Monte Carlo simulation, the key factors in the Marcus formula are summarized. Then, a localized planarization strategy is demonstrated for the hole mobility optimization of triphenylamine‐based materials with different planarity.